Analysis of strategies to meet ASHRAE S241 infectious aerosol control targets by space type and region using EnergyPlus™ simulations - Cary A. Faulkner; Cerrina Mouchref; Belal Abboushi; Meghan K. McNulty; Timothy I. Salsbury; Brett C. Singer; Michael D. Sohn; Gabe Arnold (Building and Environment, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

The ant and the grasshopper: Contrasting responses and behaviors to water stress of riparian trees along a hydroclimatic gradient - Pierre Lochin; Pauline Malherbe; Baptiste Marteau; Julien Godfroy; Flavie Gerle; John Marshall; Sara Puijalon; Michael Bliss Singer; John C. Stella; Hervé Piégay; Antoine Vernay (Science of The Total Environment, 2024)

Comparison of effectiveness and energy use of airborne pathogen mitigation measures to meet clean air targets in a prototypical office building - Cary A. Faulkner; Timothy I. Salsbury; Belal Abboushi; Cerrina Mouchref; Brett C. Singer; Michael D. Sohn; Gabe Arnold (Building and Environment, 2024)

A river runs through it: Robust automated mapping of riparian woodlands and land surface phenology across dryland regions - Conor A. McMahon; Dar A. Roberts; John C. Stella; Anna T. Trugman; Michael B. Singer; Kelly K. Caylor (Remote Sensing of Environment, 2024)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

The case for prioritizing ecology/behavior and hybridization over genomics/taxonomy and species' integrity in conservation under climate change - Camille Parmesan; Michael C. Singer; Brian Wee; Sasha Mikheyev (Biological Conservation, 2023)

Psychological and physical connections with nature improve both human well-being and nature conservation: A systematic review of meta-analyses - Gladys Barragan-Jason; Michel Loreau; Claire de Mazancourt; Michael C. Singer; Camille Parmesan (Biological Conservation, 2023)

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Colonizations cause diversification of host preferences: A mechanism explaining increased generalization at range boundaries expanding under climate change - Michael C. Singer; Camille Parmesan (Global Change Biology, 2021)
As species' poleward range limits expand under climate change, generalists are expected to be better colonists than specialists, extending their ranges faster. This effect of specialization on range shifts has been shown, but so has the reverse cause–effect: in a global meta‐analysis of butterfly diets, it was range expansions themselves that caused increases in population‐level diet breadth. What could drive this unexpected process? We provide a novel behavioral mechanism by showing that, in a butterfly with extensive ecotypic variation, Edith's checkerspot, diet breadths increased after colonization events as diversification of individual host preferences pulled novel hosts into population diets. Subsequently, populations that persisted reverted toward monophagy. We draw together three lines of evidence from long‐term studies of 15 independently evolving populations. First, direct observations showed a significant increase in specialization across decades: in recent censuses, eight populations used fewer host genera than in the 1980s while none used more. Second, behavioral preference‐testing experiments showed that extinctions and recolonizations at two sites were followed, at first by diversification of heritable preference ranks and increases in diet breadth, and subsequently by homogenization of preferences and contractions of diet breadth. Third, we found a significant negative association in the 1980s between population‐level diet breadth and genetic diversity. Populations with fewer mtDNA haplotypes had broader diets, extending to 3–4 host genera, while those with higher haplotype diversity were more specialized. We infer that diet breadth had increased in younger, recently colonized populations. Preference diversification after colonization events, whether caused by (cryptic) host shifts or by release of cryptic genetic variation after population bottlenecks, provides a mechanism for known effects of range shifts on diet specialization. Our results explain how colonizations at expanding range margins have increased population‐level diet breadths, and predict that increasing specialization should accompany population persistence as current range edges become range interiors.

Adaptive and maladaptive consequences of “matching habitat choice:” lessons from a rapidly-evolving butterfly metapopulation - Michael C. Singer (Evolutionary Ecology, 2015)

Endangered Quino checkerspot butterfly and climate change: Short-term success but long-term vulnerability? - Camille Parmesan; Alison Williams-Anderson; Matthew Moskwik; Alexander S. Mikheyev; Michael C. Singer (Journal of Insect Conservation, 2015)

Host‐associated genomic differentiation in congeneric butterflies: now you see it, now you do not - Alexander S. Mikheyev; Carolyn S. McBride; Ulrich G. Mueller; Camille Parmesan; Melanie R. Smee; Constanti Stefanescu; Brian Wee; Michael C. Singer (Molecular Ecology, 2013)
Ecotypic variation among populations may become associated with widespread genomic differentiation, but theory predicts that this should happen only under particular conditions of gene flow, selection and population size. In closely related species, we might expect the strength of host‐associated genomic differentiation ( HAD ) to be correlated with the degree of phenotypic differentiation in host‐adaptive traits. Using microsatellite and A mplified F ragment L ength P olymorphism ( AFLP ) markers, and controlling for isolation by distance between populations, we sought HAD in two congeneric species of butterflies with different degrees of host plant specialization. Prior work on E uphydryas editha had shown strong interpopulation differentiation in host‐adapted traits, resulting in incipient reproductive isolation among host‐associated ecotypes. We show here that E uphydryas aurinia had much weaker host‐associated phenotypic differentiation. Contrary to our expectations, we detected HAD in Euphydryas aurinia , but not in E. editha . Even within an E. aurinia population that fed on both hosts, we found weak but significant sympatric HAD that persisted in samples taken 9 years apart. The finding of significantly stronger HAD in the system with less phenotypic differentiation may seem paradoxical. Our findings can be explained by multiple factors, ranging from differences in dispersal or effective population size, to spatial variation in genomic or phenotypic traits and to structure induced by past histories of host‐adapted populations. Other infrequently measured factors, such as differences in recombination rates, may also play a role. Our result adds to recent work as a further caution against assumptions of simple relationships between genomic and adaptive phenotypic differentiation.

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

Geographic mosaics of species' association: a definition and an example driven by plant–insect phenological synchrony - Michael C. Singer; Carolyn S. McBride (Ecology, 2012)
Spatial mosaics occur in both evolutionary and ecological properties of species' interactions. Studies of these patterns have facilitated description and prediction of evolutionary responses of interacting species to each other and to changing environments. We propose seeking complementary understanding of community assembly and dynamics by studying ecological and mechanistic properties of mosaics. We define “species' association mosaics” as deviations from a null model in which spatial variation in the extent to which particular species interact ecologically is explained solely by variation in their densities. In extreme deviations from the null, a focal species interacts exclusively with different partners at different sites despite similar abundances of potential partners. We investigate this type of mosaic involving the butterfly Euphydryas editha and its hosts, the perennial Pedicularis semibarbata (Psem) and the ephemeral annual Collinsia torreyi (Ctor). A reciprocal transplant experiment showed that the proximate, mechanistic driver of the mosaic was variation in butterfly oviposition preference: the identity of the preferred host species depended on the site of origin of the insects, not that of the plants. In contrast, the evolutionary driver was phenological asynchrony between the insects and Ctor. Censuses showed that larvae hatching from eggs laid on Ctor would have suffered significantly greater mortality from host senescence at five sites where Ctor was avoided than at two sites where it was used. These differences among sites in phenological synchrony were caused by variation in life span of Ctor. At sites where Ctor was avoided, natural selection on host preference was stabilizing because Ctor life span was too short to accommodate the development time of most larvae. At sites where Ctor was used, selection on preference was also stabilizing because larvae lacked physiological adaptation to feed on Psem. These reciprocal forces of stabilizing selection formed a mosaic maintaining spatial variation in insect host preference that was the proximate cause of the species‐association mosaic. In the Discussion , we examine the extent to which our findings hindcast an observed anthropogenic host shift by E. editha from Psem to Ctor. This example shows that elucidation of species‐association mosaics can facilitate understanding of community evolution and dynamics.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Protandry and postandry in two related butterflies: conflicting evidence about sex-specific trade-offs between adult size and emergence time - Gabriel Nève; Michael C. Singer (Evolutionary Ecology, 2008)

Has inbreeding depression led to avoidance of sib mating in the Glanville fritillary butterfly (Melitaea cinxia)? - Sari Haikola; Michael C. Singer; Ido Pen (Evolutionary Ecology, 2004)

When random sampling does not work: standard design falsely indicates maladaptive host preferences in a butterfly - Michael C. Singer; Constantí Stefanescu; Ido Pen (Ecology Letters, 2002)
In experiments that investigate species’ interactions, individuals are often chosen at random to represent their populations. However, this practice can generate misleading results when individuals of different species do not interact at random. We illustrate this effect by examining oviposition preferences of Euphydryas aurinia butterflies from three populations using three different plant genera. We first offered each insect a randomly chosen member of its own host population and a foreign host ( Succisa pratensis ) not present in the insect’s habitat. The butterflies uniformly preferred the foreign Succisa over their own hosts. Preferences were apparently maladaptive because insects wasted time searching for a nonexistent plant. We repeated the experiment using individual hosts that had naturally received eggs in the field. The overall preference for Succisa and the appearance of maladaptation both disappeared. In the original experiments, our random choice of experimental host individuals had combined with strong within‐species discrimination by the butterflies and with overlap of acceptability between host species to obscure the true nature of host preference.

Inbreeding depression and the maintenance of genetic load in Melitaea cinxia metapopulations - Sari Haikola; Wilhelm Fortelius; Robert B. O'Hara; Mikko Kuussaari; Niklas Wahlberg; Ilik J. Saccheri; Michael C. Singer; Ilkka Hanski (Conservation Genetics, 2001)

Discrimination within and between host species by a butterfly: implications for design of preference experiments - Michael C. Singer; Joy R. Lee (Ecology Letters, 2000)
Experiments designed to reveal variation among individual parasites in preference for different host species may generate misleading results. Apparent variation in the order of preference among host species can be generated solely from variation in the strength of discriminations made within host species. We illustrate this with a study of oviposition preference in the butterfly Melitaea cinxia. All butterflies were tested on the same six individual plants, three Plantago lanceolata (P) and three Veronica spicata (V). Some insects repeatedly preferred all individual P over all individual V or vice versa. We designated these as “pure” species ranks. Other insects repeatedly produced “mixed” ranks, preferring some individual V over some P, and some individual P over some V. We show how a “mixed” rank butterfly could differ from a “pure” rank insect by discriminating either more within plant species and/or less between them. Therefore, discrimination within host species can mask or confound discrimination among species. We discuss implications for the design of preference experiments.

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)